PRAKTEK AKUNTANSI PENETAPAN NILAI BELIS PERKAWINAN SUKU LIO DESA BOKASAPE TIMUR, KECAMATAN WOLOWARU, KABUPATEN ENDE - Angelina Novita Nabo; Nikson Tameno; Siprianus G. Tefa (Jurnal Trial Balance, 2025)
Abstract This study discusses accounting practice in determining the value of belis in the marriage customs of the Lio tribe in East Bokasape Village, Wolopuru District, Ende Regency. The goal is to identify, measure, and record the value of belis in the marriage customs of the Lio tribe in East Bokasape Village. The type of research used in this study is qualitative. The type of data used is qualitative data supported by quantitative data. Data collection was obtained from observation, interviews, documentation and literature studies using Miles and Huberman data analysis techniques and using Nvivo software application tools. This research focuses on accounting practice with three (3) stages, namely, identification, measurement, and record-keeping. The results of this study are in the form of accounting science recording which is carried out simply, so that the results are found to be related to the relationship of the accounting approach in giving belis to the marriage customs of the Lio Tribe of East Bokasape Village which is a material for information and consideration about belis in accounting, including: (1) identification in belis is said to be relevant because economic transactions can be identified as a source of measurement and recording in accounting. (2) The research shows that the process of measuring belis, measured using the fair value "fair value", which is according to the market price set at that time, so that in the recognition process, the value of belisk is recorded at the stage of belis. (3) In recording Belis, the researcher provides an overview of journals and financial reports that can be used in the Belis event, meaning that this becomes a reference material in the next Belis event as evidence of documentation and consideration in the economy. Keywords: Identification, measurement, recording, Belis Customary Marriage Abstrak Penelitian ini membahas praktek akuntansi dalam penetapan nilai belis pada adat perkawinan suku Lio di Desa Bokasape Timur, Kecamatan Wolowaru, Kabupaten Ende. Tujuannya adalah untuk mengidentifikasi, mengukur, dan mencatat nilai belis dalam adat perkawinan suku Lio di Desa Bokasape Timur. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian kualitatif. Jenis data yang digunakan adalah data kualitatif yang didukung dengan data kuantitatif. Pengumpulan data diperoleh dari observasi, wawancara, dokumentasi dan studi kepustakaan dengan teknik analisis data Miles dan Huberman dan menggunakan alat bantu aplikasi software Nvivo. Penelitian ini berfokus pada praktek akuntansi dengan tiga (3) tahap yaitu, pengidentifikasian, pengukuran, dan pencatatan. Hasil penelitian ini berupa pencatatan ilmu akuntansi yang dilakukan secara sederhana, sehingga hasil ditemukan adanya keterkaitan pendekatan akuntansi dalam pemberian belis pada adat perkawinan masyarakat Suku Lio Desa Bokasape Timur yang menjadi bahan informasi dan bahan pertimbangan tentang belis dalam akuntansi antara lain: (1) pengidentifikasian dalam belis dikatakan relevan karena transaksi ekonomi dapat di identifikasi menjadi sumber pengukuran dan pencatatan dalam akuntansi. (2) penelitian menunjukan proses pengukuran belis, diukur dengan menggunakan nilai wajar “fair value” yaitu sesuai harga pasar yang ditetapkan pada saat itu, sehingga pada proses pengakuan, nilai belis dicatat pada tahapan belis itu terjadi. (3) pada pencatatan belis peneliti memberikan gambaran jurnal dan laporan keuangan yang dapat digunakan dalam peristiwa belis, artinya ini menjadi bahan acuan dalam peristiwa belis selanjutnya sebagai bukti dokumentasi dan pertimbangan dalam ekonomi. Kata Kunci: Pengidentifikasian, pengukuran, pencatatan, Belis Adat Perkawinan